Specific energy absorption study on external inversion of metal tubes / Mohd Rozaiman Aziz and Roslan Ahmad - Aziz, Mohd Rozaiman; Ahmad, Roslan (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2007)
A series of aluminum cylindrical shells are tested under axial impact condition for the numerical solutions validation of the experimental in static response. Mean load from numerical simulation as well as experiment are investigated in order to obtain the specific energy absorption. Comparison with previous researcher also made. As far as this paper concern, good agreement is observed through comparison of experimental results and numerical study.